The makers of the modern Middle East - Fraser, T. G.; Mango, Andrew; McNamara, Robert (Gingko Library, 2011)
A century ago, as World War I got underway, the Middle East was dominated, as it had been for centuries, by the Ottoman Empire. This revised edition traces those changes and the ensuing history of the region through the rest of the twentieth century. It helps readers to understand its history and the way it affects present-day events.